MicroRNAs 99b-5p/100-5p Regulated by Endoplasmic Reticulum Stress are Involved in Abeta-Induced Pathologies - Ye, Xiaoyang; Luo, Hongxue; Chen, Yan; Wu, Qi; Xiong, Yi; Zhu, Jinyong; Diao, Yarui; Wu, Zhenguo; Miao, Jianting; Wan, Jun (Frontiers in Aging Neuroscience, 2015)
Alzheimer’s disease (AD) is the most common cause of dementia. Amyloid beta (Abeta) deposition and intracellular tangles are the pathological hallmarks of AD. MicroRNAs (miRNAs) are small non-coding RNAs which have been found to play very important roles and have the potential to serve as diagnostic markers during neuronal pathogenesis. In this study, we aimed to determine the roles of miR-99b-5p and miR-100-5p in Abeta-induced neuronal pathologies. We detected the expression levels of miR-99b-5p and miR-100-5p in the brains of APPswe/PS1ΔE9 double transgenic mice (APP/PS1 mice) at different age stages and found both miRNAs were decreased at early stages while increased at late stages of APP/PS1 mice when compared with the age-matched wild type (WT) mice. Similar phenomenon was also observed in Abeta-treated cultured cells. We also confirmed that mTOR (mammalian target of rapamycin) is one of the targets of miR-99b-5p/100-5p, which is consistent with previous studies in cancer. MiR-99b-5p/100-5p have been found to promote cell apoptosis with the Abeta treatment. This effect may be induced via the mTOR pathway. In our study, we find both miR-99b-5p and miR-100-5p affect neuron survival by targeting mTOR. We also speculate that dynamic change of miR-99b-5p/100-5p levels during Abeta-associated pathologies might be attributed to Abeta-induced endoplasmic reticulum stress (ER stress), suggesting the potential role of the “ER stress –miRNAs – mTOR” axis in Abeta-related AD pathogenesis.